KNOWING “KNOWLEDGE” AND “TO KNOW”: AN OVERVIEW OF CONCEPTS - Agarwal, Abhishek (International Journal of Research -GRANTHAALAYAH, 2017)
Knowledge is a topic, widely discussed both in philosophy and in everyday life of a common man who is not aware of its principles and existing connotations. This paper attempts to explain “knowledge”, significance of “Knowing” by incorporating diverse interdisciplinary, multicultural perspectives on understanding of “Knowledge” and its concepts that we experience “knowingly or unknowingly”. It involves a discussion on wisdom-knowledge interaction, their differences and interdependence; reality and its manifestations in various aspects that talks about the nature of reality in general as a concept; and a brief essay on unexplained mystery of “Sampurna gyana” (meaning complete knowledge) and “Sarwagya” (person who knows everything) trying to understand it’s possibility in a world of infinite possibilities.